Insects and spiders associated with ornamental plants in David, Chiriqui, Panama - Collantes, Ruben Darío (2021)
The aim of this work was to identify the insects and spiders associated with ornamental plants in David, Chiriquí, Panama. For this, five random samplings were carried out in four locations, selecting 35 plant species and collecting the specimens manually. The identification of insects and spiders was made by consulting specialized documentation and photographs were taken. According to the results, the predominant species of spiders in ornamentals were Argiope argentata (Fabricius, 1775) (Araneae: Araneidae) and Leucauge venusta (Walckenaer, 1841) (Araneae: Tetragnathidae). Phytophagous insects were represented by the order Phasmatodea and Oiketicus kirbyi Guilding, 1827 (Lepidoptera: Psychidae) feeding on palm leaves (Arecaceae); three species of grasshoppers associated with Toro grass, from which Taeniopoda varipennis Rehn, 1905 (Orthoptera: Romaleidae) stood out; Scarabaeidae and Chrysomelidae (Coleoptera) feeding on Schefflera leaves. About biting-sucking species, nymphs of Lygaeidae (Hemiptera) were observed in Toro grass; while aphids (Hemiptera: Aphididae) and scales (Hemiptera: Coccidae) associated with ants (Hymenoptera: Formicidae); nymphs and adults of Membracis mexicana Guérin-Méneville, 1829 (Hemiptera: Membracidae) were found in Schefflera shoots and Ficus benjamina leaves were damaged by Gynaikothrips uzeli (Zimmermann, 1900) (Thysanoptera: Phlaeothripidae). Regarding predatory insects, only lacewing eggs and larvae (Neuroptera: Chrysopidae) and Libellulidae adults (Odonata) were found. The absence of parasitoids and the low number of species found could be associated with synthetic pesticides application, which breaks the balance of trophic interactions.